Laboratory Evaluation of Acute Toxicity of the Essential Oil of Allium tuberosum Leaves and Its Selected Major Constituents Against Apolygus lucorum (Hemiptera: Miridae). Issue 1 (7th August 2015) - Shi, Jizhe; Liu, Xinchao; Li, Zhen; Zheng, Yuanyuan; Zhang, Qingwen; Liu, Xiaoxia
Abstract : The aim of this research was to evaluate acute toxicity of the essential oil of leaves of Chinese chives, Allium tuberosum Rottler ex Spreng (Asparagales: Alliaceae) and its major constituents against Apolygus lucorum Meyer-Dür (Hemiptera: Miridae). The essential oil of A. tuberosum leaves was obtained by hydrodistillation and analyzed by gas chromatography and gas chromatography-mass spectrometry. The major constituents of the oil were sulfur-containing compounds, including allyl methyl trisulfide (36.24%), diallyl disulfide (27.26%), diallyl trisulfide (18.68%), and dimethyl trisulfide (9.23%). The essential oil of A. tuberosum leaves exhibited acute toxicity against Ap. lucorum with an LD50 value of 20.03 μg per adult. Among the main compounds, diallyl trisulfide (LD50  = 10.13 μg per adult) showed stronger acute toxicity than allyl methyl trisulfide (LD50  = 21.10 μg per adult) and dimethyl trisulfide (LD50  = 21.65 μg per adult). The LD50 value of diallyl disulfide against Ap. lucorum was 28.10 μg per adult. The results indicated that the essential oil of A. tuberosum and its major constituents may have a potential to be developed as botanical insecticides against Ap. lucorum.